STEP UP THE HEAT: A REGRESSION DISCONTINUITY ANALYSIS OF THE EFFECT OF HOME HEATING SUBSIDY ON ENERGY EXPENDITURE - Soon, Jan-Jan (International Journal of Business and Society, 2017)
Using a recent housing survey micro level dataset, this paper estimates the causal effects of receiving a home heating subsidy on different types of energy expenditure. Applying a regression discontinuity design quasi-experimental framework, identification for the causal treatment effect of energy subsidy is achieved by exploiting exogenous variations generated from the subsidy eligibility rule. Results are obtained from three model estimations: first-stage, reduced-form, and second stage estimations. The main finding from each of these estimations are: (i) energy subsidy eligibility increases the probability of receiving the subsidy, (ii) subsidy eligibility decreases energy expenditure, and (iii) subsidy receipt decreases energy expenditure. For an eligible household, its probability of receiving the subsidy increases between 2 to 8 percentage points at the threshold. Just by virtue of being eligible, such households see an approximate 8% to 25% decrease in their total energy expenditure at the threshold. Households that receive energy subsidies decrease their total energy expenditure by about half to three-quarters at the threshold. Keywords: Energy Subsidy; HEAP; Energy Expenditure; Home Space Heating; Regression Discontinuity.